Correlation as a Means of Expressing Syntactic Connections of Parenthetical Construction with Main Sentence - Yaghubyan, Marine (Armenian Folia Anglistika, 2015)
Parenthetical constructions are connected with the sentence by means of a special type of grammatical connection – correlation. The characteristic feature of this type of grammatical connection is that between the parenthetical construction and the sentence there exists a lexical connection, the grammatical expression of which is the insertion of parenthetical constructions within the sentence structure. The specific character of this type of grammatical connection is that parenthetical construction is independent of the sentence part it defines and has an independent grammatical shaping. The special type of the connection of parenthetical construction with the main sentence distinguishes the parenthetical construction from the part of the sentence which depends on its head-word. Correlation shapes the syntactic isolation of parenthetical constructions within the sentence. It is one of the main features of parenthetical construction as an independent syntactic category.
Keywords: correlation; parenthetical construction; grammatical connection; semantic connection; agreement; government; enclosure; correlative connection; upsetting; syntactic isolation